Molecular characterization of antifolates resistance-associated genes, (dhfr and dhps) in Plasmodium vivax isolates from the Middle East - Afsharpad Mandana; Motmaen Shadi; Zakeri Sedigheh; Djadid Navid (Malaria Journal, 2009)
Abstract Background In Iran, co-infections of Plasmodium vivax and Plasmodium falciparum are common and P. vivax infections are often exposed to sulphadoxine-pyrimethamine (SP). In the present study, the frequency distribution of mutations associated to SP resistance was investigated in pvdhfr and pvdhps genes from field isolates. Methods Clinical isolates of P. vivax were collected in two different malaria endemic regions in northern and south-eastern Iran, between 2001 and 2006. All 189 collected isolates were analysed for SNP/haplotypes at positions 13, 33, 57, 58, 61, 117 and 173 of the pvdhfr and 383 and 553 of pvdhps genes using nested PCR-RFLP methods Results All 189 examined isolates were found to carry wild-type amino acids at positions 13, 33, 61 and 173, while 57L and 58R and 117N mutations in pure form was detected among 1.1%, 17.5% and 26% examined samples, respectively, with no polymorphisms in different loci of dhps genes. Based on size polymorphism of pvdhfr genes at repeat region, among northern isolates, the frequency distribution for type A and B were 2.2% and 97.8% respectively. However, in southern samples the prevalence of type A, B and C were 7%, 89.5% and 7.7%, respectively. Mixed genotype infections (type B and C) were detected in only 4.2% (6/143) of southern, but in none of the northern isolates. The combination of pvdhfr and pvdhps haplotypes among all 189 samples demonstrated six distinct haplotypes. The two most prevalent haplotypes among all examined samples were I13P33F57S58T61S117I173/A383A553 (65.6%) and I13P33F57S58T61N117I173 (16.4%). Two other alleles with one point mutation I13P33F57R58T61S117I173/A383A553 and two mutations I13P33F57R58T61N117I173/A383A553 accounted for 7.4% and 9.5% of the total isolates. Conclusion The present molecular data provide important information for making decisions on population based drug use in Iran. In addition, since October 2005, with more availability of SP as first-line treatment, P. vivax isolates are more exposed to SP and the selection or spread of resistant pvdhfr and pvdhps alleles might increase in the near future in this region.